COVID-19 and Stock Market Reaction in Indonesia - Yanuar Trisnowati; Arianto Muditomo (Universitas Muhammadiyah Yogyakarta, Indonesia, 2021)
Research aims: COVID-19 Pandemic happens all over the world. Pandemic impact hits almost all elements of life, one of the affected real sectors is finance especially the stock market. This research is aimed to present the reaction of the equity market in Indonesia towards the COVID-19 pandemicDesign/Methodology/Approach: The research method that is used is the study to examine market reaction towards the pandemic and abnormal return around the occurrence by using two methods; mean-adjusted abnormal return and market model.Research findings: From the research conducted over the 10 indicators of the stock market index in Indonesia, it is concluded that 8 industrial sectors that have tenacious reaction toward the COVID-19 pandemic hit in Indonesia, where it is also found that the agriculture sector; basic and chemical industry; miscellaneous, consumer goods; property and real estate; transport and infrastructure; finance; trade, service, and investment, give stronger reactions compared with mining and manufacture.Theoretical contribution/Originality: Researches about the stock market reaction to the non-economy phenomenon have already been carried out, but the research that is specifically done to study sectoral index reaction towards the non-economy occurrences is still wide open to doing for deeper research.Practitioner/Policy implication: This research can be important information for investors to understand the behavior of stock market efficiency in Indonesia in making decisions of investmentResearch limitation/Implication: Non-economy event that becomes the subject of research is the COVID-19 pandemic that appeared and escalated fast all over the world. The researcher conducted the research and presented it as quickly as possible since the time is limited. It is meant to show a systematic and scientific thinking framework in addressing the non-economy events, but still in the context of reliability on the result of research to the same topic about the COVID-19 effect in other countries.